Enhancing the performance feedback system of the internal audit department of a government agency - Acuna, John Paul (Animo Repository, 2023)
This action research discusses how an internal audit department of a government agency addressed the lapses noted in its performance feedback system, specifically the lack of upward feedback. This issue allowed some gaps in managerial skills to remain unresolved which negatively impacts the conduct of audit engagements in the form of diminishing employee morale, unbalanced distribution of workload, and improper guidance from supervisors. Through focus group discussions, interviews, and surveys, the collaborators (myself and colleagues representing different ranks) identified the underlying causes and effects of the issue. The first cycle focused on formulating the implementation plan for the adoption of the upward feedback mechanism, including the feedback form to be used. The plan was tested through a dry run. The second cycle focused on improving the implementation plan after evaluating the results of the dry run and presenting the final version to top management for their disposition. The research achieved its goal of getting approval from management to further review and test the upward feedback mechanism crafted by the collaborators on a wider scale, involving the whole department. As they worked towards a common goal, the research resulted in stronger bond among the collaborators as well. Major findings of the research include: (1) feedback cannot be completely anonymous as feedback providers may lack accountability and (2) a well-designed upward feedback mechanism results in improved receptiveness from personnel, especially supervisors.